Analyzing the utilization of high-voltage electric fields for laser material processing - Christian Frey; Mikail Kacar; Arda Hiz; Robert Gerlach; Willem Leterme; Simon Olschok (Journal of Advanced Joining Processes)
Laser material processing has become an essential technique in industrial manufacturing in form of welding, drilling, cutting and structuring. However, process emissions such as the metal vapor plume pose a challenge, as they can impair the efficiency and precision of the laser process through reflection, absorption, and scattering. Conventional methods attempt to reduce the influence of the metal vapor plume by using shielding gases to remove the particles from the laser beam path. A novel alternative is the use of electric fields for targeted manipulation of the metal vapor to control the extinction effects. High voltage capacitors can precisely control the electric field which offers greater adaptability to a dynamic laser process. The following study investigates the utilization of high voltage capacitor configurations for generating electric fields to actively deflect metal vapor from the laser beam path during laser welding. The distribution of the electric field is analyzed using the finite element method (FEM) for the considered capacitor geometries. The weld seam geometry shows a distinct geometry depending on the selected capacitor arrangement, and the weld penetration depth decreases with the use of the electric field. The measurable trend remains preliminary, since it is assumed that the welding fume is held over the welding position by the electric field, which influences the result.